Differentiated response mechanisms of soil microbial communities to nitrogen deposition driven by tree species variations in subtropical planted forests - Hou, Zheng; Chen, Wen; Zhang, Xiaohua; Zhang, Donghui; Xing, Jinmei; Ba, Yong; Yu, Jie; Wang, Keqin; Zhang, Ya; Song, Yali (Frontiers in Microbiology, 2025)
IntroductionThe increasing rate of atmospheric nitrogen deposition has severely affected the structure and function of these ecosystems. Although nitrogen deposition is increasing globally, the responses of soil microbial communities in subtropical planted forests remain inadequately studied.MethodsIn this study, a four-year experimental simulation was conducted to assess the impacts of varying nitrogen deposition levels (CK: 0 g·N·m−2·a−1; N10: 10 g·N·m−2·a−1; N20: 20 g·N·m−2·a−1; N25: 25 g·N·m−2·a−1) on two subtropical tree species, Pinus yunnanensis Franch. and Pinus armandii Franch. High-throughput sequencing was performed using the Illumina MiSeq platform. Statistical analyses, including analysis of variance (ANOVA), linear mixed-effects models, principal coordinate analysis (PCoA), analysis of similarity (ANOSIM), redundancy analysis (RDA), random forest analysis, and structural equation modeling (SEM), were used to examine the short-term responses of soil nutrients, bacterial communities, and fungal community structures to nitrogen deposition.Results and discussionThe results showed that species differences led to variations in soil properties between the two forests, particularly a significant increase in soil pH in P. yunnanensis Franch. forests and a significant decrease in soil pH in P. armandii Franch. forests. Nitrogen addition did not significantly affect microbial diversity in either P. yunnanensis Franch. or P. armandii Franch. soils; however, forest type differences had a significant impact on bacterial diversity. The nitrogen addition significantly affected the relative abundance of specific microbial communities in both forest types, particularly altering the fungal community structure in the P. yunnanensis Franch forests, while no significant changes were observed in the bacterial community structure in either forest type. Furthermore, nitrogen addition increased the network complexity of bacterial communities in P. yunnanensis Franch. forests while decreasing network complexity in P. armandii Franch. forests. Structural equation modeling indicated that nitrogen addition regulates soil bacterial and fungal diversity in both forest types by modifying nitrogen availability.Purpose and significanceThese findings provide insights into the potential long-term impacts of nitrogen deposition on subtropical planted forest ecosystems and offer a theoretical basis for sustainable forest management and regulatory practices.